Stigmatic Transcriptome Analysis of Self-Incompatible and Compatible Pollination in Corylus heterophylla Fisch. × Corylus avellana L. - Hou, Sihao; Zhao, Tiantian; Yang, Zhen; Liang, Lisong; Ma, Wenxu; Wang, Guixi; Ma, Qinghua (Frontiers in Plant Science, 2022)
Abstract: Self-incompatibility (SI) protects plants from inbreeding depression due to self-pollination, and promotes the outcrossing process to maintain a high degree of heterozygosity during evolution. Corylus is important woody oil and nut species that show sporophytic SI (SSI). Yet the molecular mechanism of SI in Corylus remains largely unknown. Here we conducted self- (‘Dawei’ × ‘Dawei’) and cross-pollination (‘Dawei’ × ‘Liaozhen No. 7’) experiments, and then performed an RNA-Seq analysis to investigate the mechanism of pollen-stigma interactions and identify those genes that may be responsible for SSI in Corylus. We uncovered 19 163 up- and 13 314 down-regulated genes from the comparison of different pollination treatments. These DEGs were significantly enriched in plant-pathogen interaction, plant hormone signal transduction, and MAPK signaling pathway-plant. We found many notable genes potentially involved in pollen-stigma interactions and SSI mechanisms, including genes encoding receptor-like protein kinases (RLK), calcium-related genes, disease resistance genes, and WRKY transcription factors. Four up-regulated and five down-regulated DEGs were consistently identified in those comparison groups involving self-incompatible pollination, suggesting they had important roles in pollen-pistil interactions. We further identified the S-locus region of the Corylus heterophylla genome based on molecular marker location. This predicted S-locus contains 38 genes, of which 8 share the same functional annotation as the S-locus genes of Corylus avellana: two PIX7 homologous genes (EVM0002129, EVM0025536), three MIK2 homologous genes (EVM0002422, EVM0005666, EVM0009820), one aldose 1-epimerase (EVM0002095), one 3-dehydroquinate synthase II (EVM0021283), and one At3g28850 homologous gene (EVM0016149). By characterizing the pistil process during the early post-pollination phase via transcriptomic analysis, this study provides new knowledge and lays the foundation for subsequent analyses of pollen-pistil interactions.